2012
DOI: 10.1097/ftd.0b013e31825dc4a6
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Stiripentol in Children and Adults With Epilepsy

Abstract: Therapeutic drug monitoring of STP seems to be useful because of the wide variation of STP CDR, the nonlinear concentration-to-dose relationship, age-dependent pharmacokinetics, and drug-drug interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(8 citation statements)
references
References 22 publications
1
6
0
1
Order By: Relevance
“…This study confirmed the Michaelis‐Menten pharmacokinetic profile of stiripentol that was previously described in adult healthy volunteers and people with epilepsy 24, 25. Only two adverse effects (one rhinitis and one pharyngitis) were observed, unlikely related to the treatment.…”
Section: Discussionsupporting
confidence: 89%
“…This study confirmed the Michaelis‐Menten pharmacokinetic profile of stiripentol that was previously described in adult healthy volunteers and people with epilepsy 24, 25. Only two adverse effects (one rhinitis and one pharyngitis) were observed, unlikely related to the treatment.…”
Section: Discussionsupporting
confidence: 89%
“…Although an assay to measure stiripentol levels is described, it is not indicated for therapeutic purposes by the manufacturer or regulatory bodies such as Health Canada, FDA or the EU. As such, it was not available for us for the purposes of this study (18).…”
Section: Discussionmentioning
confidence: 99%
“…STP inhibits CYP3A4 and CYP2C19 engaged in the demethylation of the CLB active metabolite, leading to a two-fold increase in the concentration of the parent drug and from a three-to five-fold increase in concentration of its metabolite [167]. Plasma concentrations of other AEDs, including CBZ, PHB, PHT, VPA, diazepam, ESM and TGB, may be increased with STP co-administration [168][169][170][171]. Concomitant administration of CBD and STP may increase STP C max 1.3-fold and AUC 1.6-fold, while 7-OH-CBD and 7-COOH-CBD exposure were decreased by 29% and 13%, respectively [172].…”
Section: Stiripentolmentioning
confidence: 99%